Remodelling of the vertebral axis during metamorphic shrinkage in the pearlfish - E. Parmentier; D. Lecchini; P. Vandewalle (Journal of Fish Biology, 2004)
Body shortening was observed in the pearlfish Carapus homei during metamorphosis. The tenuis larva at first possessed a suite of osseous vertebral bodies of similar length. The reduction in both the number and size of vertebrae followed increasing decalcification, degeneration of organic tissue and shortening. This involved a complete degradation and disappearance of the caudal tip vertebrae, and there was a reduction in the size of most of the remaining vertebrae. The further development of the vertebrae began with ossification of the neural and haemal arches before that of the vertebral body. This second part of the development followed a gradient: a gradual decreases towards the caudal tip in the size of the vertebrae and their completeness.